DOI: 10.32469/10355/56215
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a morphological awareness intervention on early writing outcomes

Abstract: The purpose of this study was to determine if teaching young students how to identify and manipulate prefixes and suffixes helped them become better at spelling and writing sentences. Twenty seven students in second and third grade were identified as being "at risk" for writing difficulty, meaning they scored below the 25th percentile on a series of written language tests. Half of these students received the intervention, which taught prefixes and suffxies, also known as morphological awareness, while the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 105 publications
0
17
0
2
Order By: Relevance
“…Here, we extend previous work to provide evidence that these phonological skills play a key role for reading decoding, sight word reading and encoding (i.e., spelling). This may seem counterintuitive, given that English is a morpho‐phonemic language, and it is posited that with increased experience with texts, children learn to recognize and use the morphological patterns to read and write (Carlisle, 1995; Fracasso, Bangs, & Binder, 2016; Singson, Mahony, & Mann, 2000). Additionally, given the opaque orthographic system of English language, more dependence on the lexical route is expected (Coltheart, Rastle, Perry, Langdon, & Ziegler, 2001), which goes against the present study's results about the involvement of phonological route by adult readers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we extend previous work to provide evidence that these phonological skills play a key role for reading decoding, sight word reading and encoding (i.e., spelling). This may seem counterintuitive, given that English is a morpho‐phonemic language, and it is posited that with increased experience with texts, children learn to recognize and use the morphological patterns to read and write (Carlisle, 1995; Fracasso, Bangs, & Binder, 2016; Singson, Mahony, & Mann, 2000). Additionally, given the opaque orthographic system of English language, more dependence on the lexical route is expected (Coltheart, Rastle, Perry, Langdon, & Ziegler, 2001), which goes against the present study's results about the involvement of phonological route by adult readers.…”
Section: Discussionmentioning
confidence: 99%
“…Morphemes are the smallest meaningful units in English language, and morphological awareness (MA) is defined as the ability to identify and manipulate these meaningful parts of words, such as root words, suffixes, and affixes (Carlisle, 1995; Law, Wouters, & Ghesquière, 2015; Tops et al, 2014). In English, spelling not only reflects the phonemic but also the underlying morphological form of a word.…”
Section: Morphological Awarenessmentioning
confidence: 99%
“…Previous studies investigated whether morphological awareness instructions improved students' spelling abilities. For example, Carlisle [58], using instructions in morphological awareness, studied the impact on spelling for second and third graders. The results showed that the intervention enhanced the students' spelling ability.…”
Section: Related Studiesmentioning
confidence: 99%
“…Awareness of the morphological structure of words and their grammatical functions plays an important role in linking the degree of lexical knowledge to the ability of learners to construct sentence structures (Berninger, Nagy, & Beers, 2011;Carlisle, 2016). Awareness of morphology could help writers build complex sentence structures by using various forms of words.…”
Section: Morphological Awareness and Writingmentioning
confidence: 99%
“…The relationship between morphological awareness and learners' spelling skills has also been examined (e.g. Carlisle, 2016;Dornay, 2017;Kirk & Gillon, 2009). However, the relationship between morphological awareness and academic writing remains unknown (Asaad & Shabdin, 2019a).…”
Section: Introductionmentioning
confidence: 99%